The X-ray spectroscopic diagnosis of laser-produced plasmas, with emphasis on line broadening - LUNNEY, JAMES GERARD (American Physical Society, 1980)
A detailed account is given of the x-ray spectroscopic diagnosis of plasmas formed by exploding pusher microballoons. The measurements of the electron temperature from the shell and from the core is described. A method for self-consistently fitting all the observed lines of one state of ionization is shown, giving a diagnosis for the electron density and the opacity. Further, it is shown that the self-consistency is only achieved when full line-broadening calculations, taking into account the shifts and asymmetries dependent on the charge of the emitter, are used for the optically thin profiles. It is also shown that non-local-thermodynamic-equilibrium effects are important in the description of the radiation transfer.
PUBLISHED
Keywords: Physics